Follicular wave dynamics and Growth factors gene expression in Braford heifers - Reineri, Pablo Sebastian; Coria, María Sumampa; Callejas, Santiago; Palma, Gustavo Adolfo (Wiley, 2020)
The objectives of the present study were (experiment 1) to characterized development and dynamics of the dominant follicles (DF) and the corpus luteum (CL) to determine patterns of two (W2) and three (W3) follicular waves in beef heifers, and (experiment 2) to determine gene expression of growth factors gene expression in follicular cells of W2 and W3 heifer. Twenty‐eight Braford heifers were used. Dominant follicular and CL were monitored daily by ultrasonography to identify the development W2 and W3 in heifers. Pre‐ovulatory DF were aspirated on day 19 in W2 and on day 22 in W3 heifers. In W2 and W3, follicular cells (FC) of gene expression of growth differentiation factor 9, bone morphogenetic protein 15 (BMP15), fibroblast growth factor basic, transforming growth factor beta receptor 1, bone morphogenetic protein receptor type IB and fibroblast growth factor receptor 2 were evaluated. The regression of the DF of the first follicular wave and the emergency of the DF of the second follicular wave began later in the heifers W2 than in W3 (p = .02 and p < .01). The regression of the CL began earlier in the W2 than in W3 group (p < .01). Gene expression of growth factors and receptors was similar between groups. However, higher relative levels of BMP15 was observed in W2 group (p = .07). Results propose that wave patterns were regulated by the development time of the DF in the first wave and the life of the CL. Furthermore, higher levels of BMP15 could produce shorter life of CL. The present work suggest that ultrasonography associated with molecular assays could be used as an easy and effective tool to characterize follicular wave patterns.